Transforming digital literacy services through virtual reading rooms - Sjuchro, Dian Wardiana; Fitriana, Rina; Priana, Ronny Yudhi Septa (Jurnal Kajian Informasi dan Perpustakaan, 2026)
Background: The development of digital technology and changes in information access patterns encourage libraries in educational institutions to transform literacy services into digital forms, one of which is the virtual reading room, an alternative reading service, such as Universitas Terbuka (UT)’s digital library. Purpose: This study aimed to analyze the transformation of digital literacy services through virtual reading rooms in supporting information access, utilization of digital sources, and user digital literacy practices. Methods: This research used a qualitative case study approach. Data were obtained through observations of the virtual reading room platform and in-depth interviews with two management representatives, one active user tutor, and eight UT student representatives from various service areas. Interview data were analyzed to answer research questions. Results: Findings indicated that Virtual Reading Rooms had transformed libraries from physical reading and discussion spaces into digital services accessible beyond spatial and temporal constraints. This transformation expanded access to integrated academic resources that supported students' daily learning activities. Findings also revealed that tutors and students continued to face challenges related to disparities in digital competency, the ability to use digital resources, and unequal digital infrastructure across regions. Additionally, challenges remained in service management and long-term sustainability. Conclusion: Virtual reading rooms are a relevant and strategic form of digital literacy service transformation to address the need for information access in the digital era. Implications: These findings offer practical guidance for libraries and educational institutions for developing adaptive, sustainable digital literacy services, and are expected to contribute to the literature on digitalization and libraries' digital transformation.